Nutritional knowledge of team sport athletes - McDonald, C. V.; McSorley, E. M.; McNeilly, A.; Magee, P. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Nutritional Knowledge (NK) and the coinciding decisions Team Sport Athletes (TSA) make in relation to their dietary intake can exert acute and long-term effects on performance, recovery, body composition and training adaptations. This study aimed to assess the NK of male and female TSA using the validated nutrition for sport knowledge questionnaire (NSKQ) which was administered via REDCap. Total participants n=756, (male n=493 (65%), female n=263 (34%)) included, Gaelic Football n=463 (61%), Hurling n=42 (6%), Camogie n=39 (5%), Rugby n=107 (14%), Football n=104 (14%). TSA were recruited across elite (County, Country, Province) n=274 (36%) and non-elite (Club, University) n=480 (64%) levels. TSA had an average total NK score of 50±13%, considered "average" (50-65%) and scores in all NSKQ sub-sections were "average" or below. NK was considered "poor" (0-49%) in the following subsections: micronutrients (43±20%), sports nutrition (47±18%) and supplementation (36±19%). A one-way ANOVA indicated a difference between sports (p= 0.021). Rugby (55±12%) had a higher total NK score compared to both Gaelic (50±13% p= 0.007) and Camogie (48±15% p= 0.044). Rugby players had an "average" (59±13%) knowledge of macronutrients and scored higher (p= 0.019) in this section in comparison to Camogie who scored "poor" (49±18%). The NK of micronutrients and supplements was "poor" for all sports. Independent samples t-tests revealed a difference in micronutrient (male 40±20%, female 48±20% p= <.001) and alcohol sub-sections between sexes (male 60±19%, female 64±18% p= <.001) with females scoring higher in both. Elite athletes scored higher in the weight management (elite 59±16%, non-elite 56±18% p= 0.041) and sports nutrition (elite 49±17%, non-elite 45±18% p= 0.011) sections than non-elite athletes albeit scores fell within the same category. The NK of TSA is sub-optimal and similar between groups. TSA may benefit from a NK intervention, which subsequently may improve diet, health and performance.